2019
DOI: 10.1080/21691401.2019.1600530
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Long non-coding RNA SNHG16 reduces hydrogen peroxide-induced cell injury in PC-12 cells by up-regulating microRNA-423-5p

Abstract: Functions of long non-coding RNAs (lncRNAs) have been widely probed in spinal cord injury (SCI). But, the influences of lncRNA-small nucleolar RNA host gene 16 (lncRNA-SNHG16) is still not well documented in SCI. The study explored the impacts of SNHG16 on H 2 O 2-injured PC-12 cells. PC-12 cells were disposed with H 2 O 2 , cell viability, apoptosis, autophagy and ROS level were detected. RT-qPCR was executed to explore SNHG16 or miR-423-5p expression in H 2 O 2-stimulated cells. After transfection with pc-SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…In very recent studies, lncRNA SNHG5 has been shown to promote astrocytes and microglia viability in SCI [33]; and lncRNA ZNF667-AS1 impacts potential function in promoting recovery of SCI [34]. Moreover, lncRNA SNGH16 is shown to reduce H 2 O 2 -disposed cell injury in PC-12 cells, providing a new reference for remedying SCI [35]. These data suggest that lncRNAs may be pivotal factors in SCI.…”
Section: Discussionmentioning
confidence: 96%
“…In very recent studies, lncRNA SNHG5 has been shown to promote astrocytes and microglia viability in SCI [33]; and lncRNA ZNF667-AS1 impacts potential function in promoting recovery of SCI [34]. Moreover, lncRNA SNGH16 is shown to reduce H 2 O 2 -disposed cell injury in PC-12 cells, providing a new reference for remedying SCI [35]. These data suggest that lncRNAs may be pivotal factors in SCI.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, SNHG16 is also a member of the lncRNA molecule, and several studies have indicated that it can promote the progression of malignant tumors. Furthermore, SNHG16 reverses LPS-induced inflammatory response in neurosepsis [29] and also attenuates hydrogen peroxide-induced PC12 neuronal damage [30]. In the present study, we found that the neuroprotective effect of DEX was closely related to the upregulated expression of SNHG16, while the neuroprotective effect of DEX on OGD-induced neuron injury was significantly decreased after knocking down SNHG16.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies have shown that upregulation of miRNA-423-5p significantly decreases cell proliferation and migration (Ge et al, 2018;Guo et al, 2018). In a very recently published study, Liu et al demonstrated that promoting miR-423-5p expression reduces hydrogen peroxide-induced PC-12 cell injury (Liu et al, 2019). We speculate that miR-423-5p upregulation, which was induced by a reduction in the level of circRNA_01477 following hemisection SCI in rats, affects regeneration by inhibiting cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 65%